Impact of grain boundaries on efficiency and stability of organic-inorganic trihalide perovskites - Zhaodong Chu (Nature Portfolio, 2017)
Probing the nanoscale photoconductivity of methylammonium lead triiodide is important for understanding the microstructures of the solar cell devices, but scanning probe methods suffer from sample degradation. Here Chu et al. solve the problem with noncontact microwave impedance microscopy.